IN THE MEDIA SPACE, ARTIFICIAL INTELLIGENCE: THE DEVELOPMENT OF WORLDVIEW IN MODERN HISTORY - Tadjibayeva Rukhshona Oktamovna (Web of Journals Publishing, 2025)
The rapid evolution of artificial intelligence in the context of the media space has markedly altered the development of worldview in modern history. The advent of digital technologies and their integration into everyday life have influenced the processes by which individuals and societies form, disseminate, and revise their own understandings of reality. Traditional factors such as culture, religion, and education retain their importance, yet the modern era is uniquely characterized by the proliferation of mediated content powered by algorithms and intelligent systems. Artificial intelligence, functioning at the intersection of data analysis, language processing, and automated decision-making, increasingly shapes the ways people perceive themselves, others, and the wider world.
Keywords: Artificial Intelligence, media space, modern history, worldview, digital society, information technology, communication, youth, mass media, digital literacy.